2014
DOI: 10.1097/gme.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soy isoflavones on thyroid hormones in intact and ovariectomized cynomolgus monkeys (Macaca fascicularis)

Abstract: Objectives Soy isoflavones are commonly used to alleviate menopause-related symptoms. Menopausal women are at an increased risk for hypothyroidism and there are concerns that isoflavones may be detrimental to thyroid health. The aim of this study was to examine the effects of soy protein and isoflavones on thyroid function and the relationship between thyroid and ovarian function. Methods Adult female cynomolgus monkeys (Macaca fascicularis) were randomized to consume two diets differing only in protein sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 47 publications
1
13
0
2
Order By: Relevance
“…In line with our data Silverstein et al. reported that in ovariectomized monkeys long time ISO exposure increased T4 levels and thereby prevented the decline of T4 levels due to OVX .…”
Section: Discussionsupporting
confidence: 93%
“…In line with our data Silverstein et al. reported that in ovariectomized monkeys long time ISO exposure increased T4 levels and thereby prevented the decline of T4 levels due to OVX .…”
Section: Discussionsupporting
confidence: 93%
“…The potential of isoflavones to influence the thyroid system in vivo was supported by results obtained in different animal studies (Chang and Doerge 2000 ; Divi et al 1997 ; Doerge and Sheehan 2002 ; Silverstein et al 2014 ; Sosic-Jurjevic et al 2014 ; White et al 2004 ). Chang and Doerge ( 2000 ) reported that the consumption of a standard soy-based rodent diet reduced TPO activity in rats by approximately 50% if compared to a soy-free diet.…”
Section: Effects Of Isoflavonesmentioning
confidence: 78%
“…The Panel acknowledged that the potential effects of isoflavones on thyroid endpoints may have been investigated in other animal models, such as juvenile or non-OVX animals. However, the differences in thyroid physiology between the rat and the human make extrapolation from rodents to humans problematic (see, for example, explanation reported in the publication by Silverstein et al (2014): 'Studies using animal models can control for many of the environmental variables thought to influence thyroid function. Controlled experiments with rodents demonstrate that isoflavones induce increases in serum T4 concentration.…”
Section: Discussion On Results From Animal Studies Reporting Effects mentioning
confidence: 99%
“…There were no statistically significant changes in the levels of T 3 or TSH in the treated animals compared with OVX controls. However, treatment with isoflavones preceded ovariectomy in the animals, so that these animals were intact when the treatment started (Silverstein et al, 2014).…”
Section: Results From Animal Studiesmentioning
confidence: 99%